(untitled) - A T Fernando (Đà Nẵng, 1996)
Sách gồm 120 bài luận văn được chọn lọc theo những đề tài hiện tại liên quan đến thực tế cuộc sống
Keywords: english language - compostion and exercises,english language - textbooks for foreign speakers,test of english as a foreign language - study guides